Penggunaan Tehnologi Pendidikan Dalam Pembelajaran Jarak Jauh Bagi Siswa Tingkat SD/MI Pada Masa Pandemi Covid-19 - Salsabila, Unik Hanifah; Ramadhan, Naufal Fauzi; Putri, Mutia Eka; Nurjannah, Nurjannah; Jayanti, Gita Dwi (EDUCARE: Journal of Primary Education, 2020)
Technology is very important in this day and age. There are so many fields that use technology, one of which is in the field of education. Even though Indonesia is still in a situation of the Covid-19 pandemic, education must remain number one by maximizing technology, especially in the field of communication. In this study discussed the role of technology during the distance learning process, especially for students at the SD / MI level. The formulation of the problems in this study are (1) How is the distance learning process using educational technology media for SD / MI students during the Covid-19 pandemic?; (2) What are the problems that occur in the distance learning process using educational technology media for SD / MI students during the Covid-19 pandemic?; (3) What is the solution to problems in the distance learning process by using educational technology media for SD / MI students during the Covid-19 pandemic? While the method used to answer the formulation of the problem is qualitative research with an analytic description approach, interviews and literature study, the focus of which is the role of technology and educational media for students at the SD / MI level during the Covid-19 pandemic. The results showed that the distance learning process was carried out using Zoom Cloud Meeting media, WhatsApp group and Google Classroom. The problem that occurs during the distance learning process is usually a signal problem that is not good and sometimes students feel bored when doing online learning so they are playing, lying down, and eating snacks. The solution that the teacher takes to overcome this problem is to provide weekend projects on Saturdays and Sundays. Tehnologi merupakan hal yang sangat penting di masa sekarang ini. Banyak sekali bidang yang memanfaatkan teknologi, salah satunya di bidang pendidikan. Meskipun Indonesia masih berada dalam situasi pandemi Covid-19, namun pendidikan harus tetap di nomor satukan dengan memaksimalkan teknologi khususnya bidang komunikasi. Di dalam penelitian ini dibahas mengenai peran teknologi selama proses pembelajaran jarak jauh terutama bagi peserta didik pada tingkat SD/ MI. Rumusan masalah dalam penelitian ini yaitu (1) Bagaimana proses pembelajaran jarak jauh dengan menggunakan media teknologi pendidikan bagi Siswa SD/MI di Masa pandemi Covid-19?; (2) Apa saja permasalah-permasalahan yang terjadi dalam proses pembelajaran jarak jauh dengan menggunakan media teknologi pendidikan bagi Siswa SD/MI di Masa pandemi Covid-19?; (3) Bagaimana solusi permasalahan dalam proses pembelajaran jarak jauh dengan menggunakan media teknologi pendidikan bagi Siswa SD/MI di Masa pandemi Covid-19? Metode Penelitian yang digunakan adalah penelitian Kualitatif dengan pendekatan deskripsi analitik, wawancara dan studi literatur kepustakaan. Hasil penelitian ini menunjukkan (1) proses pembelajaran jarak jauh dilakukan dengan menggunakan media Zoom Cloud Meeting, Whatsapp grup dan Google Classroom. (2) Permasalahan yang terjadi pada saat proses pembelajaran jarak jauh adalah adanya kendala sinyal yang kurang bagus dan terkadang siswa merasa bosan ketika sedang melakukan pembelajaran daring sehingga mereka sambil bermain, tiduran, dan memakan cemilan. (3) Solusi yang dilakukan oleh guru untuk mengatasi permasalahan tersebut adalah dengan memberi weekend project di hari Sabtu dan Ahad.